2016
DOI: 10.4103/0377-4929.174817
|View full text |Cite
|
Sign up to set email alerts
|

Rare and unusual isolates of viridans streptococci from the human oral cavity

Abstract: To the best of our knowledge, this is the first report of isolation of these rare and unusual strains from the human oral cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Non-mutans streptococci represented the predominant commensals of the microbiota from oral swabs of WT and KO mice, consistent with previous observations in humans (Lazarevic et al, 2009) as well as laboratory mice (Chun et al, 2010). S. thoraltensis was isolated previously from human subgingival plaque of patients with periodontitis (Dhotre et al, 2016). S. azizii was earlier isolated from the oral cavity of inbred C57BL mice (Braden et al, 2015) and the uncultured species of streptococcus was found in the epidermis of mice, likely transferred orally during grooming (Grice et al, 2008).…”
Section: Amylase Expression In Humans and Cariessupporting
confidence: 88%
“…Non-mutans streptococci represented the predominant commensals of the microbiota from oral swabs of WT and KO mice, consistent with previous observations in humans (Lazarevic et al, 2009) as well as laboratory mice (Chun et al, 2010). S. thoraltensis was isolated previously from human subgingival plaque of patients with periodontitis (Dhotre et al, 2016). S. azizii was earlier isolated from the oral cavity of inbred C57BL mice (Braden et al, 2015) and the uncultured species of streptococcus was found in the epidermis of mice, likely transferred orally during grooming (Grice et al, 2008).…”
Section: Amylase Expression In Humans and Cariessupporting
confidence: 88%
“…Our patient worked in an auto repair shop, had an indoor cat and had no exposure to farm animals. Dhotre S et al report S. pluranimalium being isolated from subgingival dental plaque of a patient with periodontitis following tooth extraction [15]. An extensive literature review revealed that the bacterium was isolated from a blood culture in a patient after dental piezocision procedure following transient bacteremia (with negative blood culture before the procedure) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the bacterium was performed using the Vitek 2 system, similar to our article. Analysis of the antimicrobial resistance of Streptococcus thoraltensis isolated from patients with periodontitis showed resistance to ampicillin, cefepime, cefotaxime, and ceftriaxone [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We included nine papers that describe infections produced by Streptococcus thoraltensis, emphasizing the heterogenicity of the infections this pathogen may produce [22][23][24][25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%